The Role of a Harmonious Family in Shaping Tolerant Attitudes in a Multicultural Society - Firdaus, Ahmad Zainul; Muhammad, Adamu Abubakar; Haerunnisa, Haerunnisa; Supriyadi, Supriyadi; Kurniawan, M. Rafli (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This study explores the role of harmonious families in shaping attitudes of tolerance within multicultural societies, analyzed through the lens of symbolic interaction theory. In this context, a harmonious family serves as the primary social unit that provides a foundation for individuals to understand and appreciate social, cultural, and religious differences. Using a qualitative research approach based on a literature review, the study examines how symbolic interactions within the family, including open communication and constructive conflict resolution, foster tolerant attitudes toward diversity. The analyzed data indicate that harmonious families can instill values of empathy, fairness, and respect for differences, which are essential in multicultural societies. The study finds that families with open communication patterns and strong emotional support are more likely to produce individuals capable of resolving conflicts peacefully and contributing to inclusive communities. However, the study acknowledges limitations in empirical data and recommends further field research to explore the relationship between harmonious families and the development of tolerance in diverse environments. The findings of this study are expected to provide insights for policymakers and educators in strengthening the role of families in creating tolerant and peaceful societies.